ChemInform Abstract: Three‐Component Synthesis of Poly‐Substituted Tetrahydroindoles Through p‐TsOH Promoted Alkoxylation. Issue 39 (5th September 2013) - Shi, Qing‐Qing; Fu, Li‐Ping; Shi, Yu; Ding, Hua‐Qin; Luo, Jing‐Hua; Jiang, Bo; Tu, Shu‐Jiang
Abstract Optimized conditions allow a sequential alkoxylation/heterocyclization of arylglyoxal monohydrates, alcohols and enaminones to produce the title species in a short reaction time.